De-listing cases before EU courts : restrictive measures concerning Syria and Ukraine - Muráňová, Petra; Trávníčková, Zuzana, 1977-; Lobastova, Svetlana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
This master thesis deals with the de-listing cases that were brought before the General Court of the EU in regard to the two autonomous sanction regimes of the European Union, sanctions imposed in view of the situation in Syria and Ukraine. The thesis uses data from the database of the Court of Justice of the European Union to fulfill the goal of assessing how successful the applicants in their de-listing applications were. In addition, thesis also deals with additional questions, concerning the average duration of de-listing cases and the distribution of the applications lodged, based on the type of applicant. The outcome of the master thesis is the finding, that the results differ for the regimes researched, and no general conclusion can be made. When comparing the analyzed cases, it was found that applicants for de-listing were more successful in the case of Ukraine than Syria.
Vedoucí práce: Zuzana Trávníčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses